Exploring feminisms on Instagram - Sofia P. Caldeira (Journal of Digital Social Research)
Over the past decade, Instagram has become increasingly popular and embedded in the contemporary experience of everyday feminisms. The platform allows for the co-existence of political, personal, mundane, and aesthetically-oriented content, created by both established feminist actors and “ordinary” people (i.e. not activists, career politicians, or celebrities). While feminist media studies have long studied similar practices of online feminism, historically the discipline has tended to privilege qualitative approaches, rather than more quantitatively-oriented digital methods approaches. However, the study of feminist expressions on Instagram can benefit from a critical engagement and selective embrace of some possibilities enabled by digital methods.This article offers a reflection on the use of digital methods’ tools and strategies informed by a feminist media studies theoretical and epistemological lens. This draws on an exploratory case study conducted by the author, which combined qualitative and digital methods to explore a wide landscape of feminist hashtags on Portuguese Instagram. Grounded on this case, the article examines the methodological possibilities and challenges brought by digital methods, and the tensions that can arise from their combination with qualitative feminist approaches. It explores how digital analysis tools can be adopted in combination with qualitative analysis, allowing for the emergence of new insights, critical engagements with large amounts of data, intuitive explorations of datasets, while still allowing to zoom in on specific content for in-depth qualitative engagements. Finally, it also reflects on the ethical implications of a feminist approach to digital methods at the data collecting stage, positing methodological alternatives grounded on a feminist ethics of care.